Design and fabrication of composite beam - Woon, Terence. (2009)
Carbon fibre reinforced polymers are commonly used in widespread applications in many industries due to its enhanced mechanical properties and low density. With the increasing number of applications, carbon fibre reinforced composites are now used for load bearing applications such as the floor beams in aircraft bodies and wing structures.